PENGARUH DOSIS RAGI DAN PENAMBAHAN GULA TERHADAP KUALITAS GIZI DAN ORGANOLEPTIK TAPE BIJI GANDUM - Jalalina Abdillah; Nugraheni Widyawati; - Suprihati (Agric, 2014)
Tape yeast in certain dose is required in making tape. Addition of 5% sugar could increase the sweetness as well as energy for the microorganissm. The experiment about the effect of yeast dosage and sugar addition on the quality of wheat grain tape in the Laboratory of Faculty of Science and Mathematics Satya Wacana Christian University started from 29th February until 23rd April 2012. This research used Randomized Block Design (RBD) with six treatments as follows: 1% yeast; 2% yeast; 3% yeast; 1% yeast with sugar; 2% yeast with sugar; 3% yeast with sugar. Finally, data of the result were analyzed using analysis of variance (ANOVA) and honestly significant difference (HSD) at 5% level. The research showed that: 1) 1% yeast dose had the highest quality of wheat tape compared to 2% and 3% yeast dose, 2) 1% yeast dose with sugar gave the best taste from organoleptic test.